2018
DOI: 10.1371/journal.pone.0201207
|View full text |Cite
|
Sign up to set email alerts
|

Overview of three influenza seasons in Georgia, 2014–2017

Abstract: BackgroundInfluenza epidemiological and virologic data from Georgia are limited. We aimed to present Influenza Like Illness (ILI) and Severe Acute Respiratory Infection (SARI) surveillance data and characterize influenza viruses circulating in the country over three influenza seasons.MethodsWe analyzed sentinel site ILI and SARI data for the 2014–2017 seasons in Georgia. Patients’ samples were screened by real-time RT-PCR and influenza viruses isolated were characterized antigenically by haemagglutination inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
(27 reference statements)
6
6
0
Order By: Relevance
“…Both were in winter time. Kurskaya and Machablishvili [3,6] reported that the positive rate of in uenza increased with age, which is consistent with us. Kurskaya and Dong [3,9] also reported that the highest detection rate of in uenza was in winter, Althouse [17] reported that the peak of in uenza appeared in the middle of spring (April to June).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both were in winter time. Kurskaya and Machablishvili [3,6] reported that the positive rate of in uenza increased with age, which is consistent with us. Kurskaya and Dong [3,9] also reported that the highest detection rate of in uenza was in winter, Althouse [17] reported that the peak of in uenza appeared in the middle of spring (April to June).…”
Section: Discussionsupporting
confidence: 90%
“…Respiratory virus is the main cause of infection [2]. Nasopharynx swabs or oropharynx swabs are commonly used as the pathogen detection samples of ARIs [3,5,6]. In this study, the detection of four respiratory viruses (ADV, FLUA, FLUB, and RSV) in oropharyngeal swabs of 103210 children with ARIs was analyzed retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] In other countries, this second wave of INF B viruses were also observed in the season. 13 Concerning to the clinical findings, symptoms caused by influenza B virus were remarkably similar to those caused by influenza A virus, and included fever, headache, cough, somnolence, myalgia, abdominal pain, vomiting and conjunctivitis, as observed by other authors. 19,20 We found a higher proportion of males among INF B infections, which also caused more prostration than INF A infections.…”
Section: Discussionsupporting
confidence: 70%
“…12 In three consecutive influenza seasons, other authors detected 48% of influenza in ILI episodes in children and adolescents aged five to 14 years, a similar age range of the present cohort. 13 Additionally, the use of robust diagnostic tests in multiplex platforms enhanced the likelihood of influenza diagnosis due to superior sensitivity of these new assays. 14 It is well established that INF A and INF B co-circulate annually.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory viruses are the main cause of infection [2]. Nasopharynx swabs or oropharynx swabs are commonly used for pathogen detection of ARIs [3,7,8] . In this study, the detection of four respiratory viruses (ADV, FLUA, FLUB, and RSV) using oropharyngeal swabs from 103,210 children with ARIs was analyzed retrospectively.…”
Section: Discussionmentioning
confidence: 99%